If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1z + 8y = 24 Reorder the terms: 8y + 1z = 24 Solving 8y + 1z = 24 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1z' to each side of the equation. 8y + 1z + -1z = 24 + -1z Combine like terms: 1z + -1z = 0 8y + 0 = 24 + -1z 8y = 24 + -1z Divide each side by '8'. y = 3 + -0.125z Simplifying y = 3 + -0.125z
| 6(4+1.5x)-12=39 | | x^3+x^7= | | 2x-=11 | | t-5=-18 | | 9x^2+12xy+4y^2+18x+12y+8=0 | | 63=-49+n | | 3/2y=20 | | 2x+3y-4z=0 | | 2x+3y-42=0 | | 17x+3y=-11 | | 2B+(B/2-2)+B=180 | | -3a-6a+10a+5=10 | | 400/3=163 | | -2/5=-2/3u+1/4 | | x=48-4y | | 15x-201=35 | | 12(48+24)= | | 8x+2=x+5 | | 2x^2-20x+45=0 | | 11x-88= | | 4w-1(1-w)=-38 | | (4+x)/2=-1 | | 1/2x+2/3=-6x-3 | | [-10v+3]=83 | | 4(3x-2)=-2x+7 | | -3(u+6)=4u-4 | | 9x+18=3x+78 | | 2(-x+3)-3=2(5-5x)+1 | | -2(k-5)=-4(k-4) | | -u^2+8u+12=0 | | 2x-(4+7x)=3(x+8) | | 12b=-96forb |